Potret Lokalisasi Gang Dolly dalam Perspektif Patologi Sosial - Akmal Saputra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2015)
Prostitution, localization and freesex is a phenomenon that is familiar in the midst of the people of Indonesia, including the case